Mapeamento do zoneamento da Bacia Hidrográfica do Ribeirão Paraíso, São Manuel-SP, visando o planejamento e gestão ambiental - Pollo, Ronaldo Alberto [UNESP] (2017)
The present work aimed to map the Environmental Zoning of the Ribeirão Paraíso - SP watershed, which has in its own quantity of springs in its upstream and being used for the urban and industrial supply in the São Manuel- SP county, where a portion is inserted in the Environmental Protection Area - APA perimeter Botucatu- SP, that was considered a recharge area of the Guarani Aquifer. With use of satellite images SPOT 5, LANDSAT 8 in Geographic Information System besides the relief and soil data, they were delimited as cover and soil land use and through crossings was got the mappings of the environmental fragility potential, that represents the natural enviroments and emergent environmental fragility, that represent the anthropic enviroments. The GIS was facilitated by the processing and analysis of the set of environmental variables. The integrated analysis of aspects about the permanent conservation, resulting from the delimitation of homogeneous areas, from the environmental zoning map of the study area, in which four Zones have been defined with their respective environmental units according to their potentials, limitations and restrictions about the of use of physical nature, environmental and juridical. In their most varied environments they stand out in the study area with systematized information about the medium, the Environmental Zoning showed as an important instrument for the project and guidance in the definition of policies and strategies for environmental planning, which in addition to presenting specific suggestions and preventive measures for a sustainable management of natural resources, through its information, becomes an instrument capable of guiding and coroborating with other instruments of environmental planning and management.